Química mineral da clorita e muscovita do depósito de Au ± Cu disseminado do Pé Quente, na Província Aurífera de Alta Floresta (MT) - Calaboni, Rodrigo [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The Alta Floresta Gold Province (AFGP), northern region of Mato Grosso State, corresponds to a crustal segment inserted in the southern sector of the Amazon Craton, constituted by plutonic, volcanic and volcano-sedimentary sequences of the Paleo-Mesoproterozoic. The primary gold mineralizations sum up more than one hundred small deposits, concentrated along the Peru-Trairão belt, of NW-SE direction. The muscovitic alteration (muscovite + quartz + pyrite) and chloritic alteration (chlorite ± quartz) correspond to important hydrothermal typologies in the majority of deposits in the province. The muscovitic alteration, for example, represents the hydrothermal alteration with chronologic and spatial relation to the main mineralization zones, whereas the chloritization usually represents a later hydrothermal stage. Although the main geological attributes of this deposit are relatively well equated, mineral chemistry studies are still scarce. In this context, this study has the main objective of discussing the mineral chemistry of chlorite and muscovite for the Au ± Cu Pé Quente deposit (located on the boundaries between the municipalities of Terra Nova do Norte and Peixoto de Azevedo, MT). The mineral chemistry studies followed the petrographic characterizations of four distinct textural types of muscovite: anedric, radial, subeuedral and intercleavage; besides two varieties of chlorite: anedric and pseudomorphic. The chemical classification showed homogeneity in both the crystal variations, with the muscovite resulting in phengitic composition, while the chlorite is essentially brunsvigitic. The chlorite geothermometry indicates temperatures around 245 and 265 °C, while the muscovite geobarometry indicates pressures around 0.92 and 3.03 kbar. Methods discussing the distance of the chlorite crystals to the hydrothermal fluids sources, through chemical ratios, indicates distances between 1,150 and 1,668 meters. The pressure results indicates the...

A Província Aurífera de Alta Floresta (PAAF), norte do Mato Groso, corresponde a um seguimento crustal inserido no setor sul do Cráton Amazônico, constituído por sequências plutônicas, vulcânicas e vulcanossedimentares do Paleo ao Mesoproterozóico. As mineralizações auríferas primárias somam mais de uma centena de depósitos de pequeno porte e ocorrem concentradas ao longo do alinhamento Peru-Trairão de direção NW-SE. As alterações com muscovita (muscovita + quartzo + pirita) e clorítica (clorita ± quartzo) correspondem a importantes tipologias hidrotermais recorrentes na grande maioria dos depósitos da província. A alteração com muscovita, por exemplo, representa a alteração temporal e espacialmente relacionada às principais zonas mineralizadas, enquanto que a cloritização usualmente representa estágios mais tardios e distais do sistema magmático hidrotermal. Embora os principais atributos geológicos do depósito estejam relativamente bem equacionados, estudos de química mineral da clorita e muscovita ainda são escassos. Neste contexto, este trabalho tem a temática do estudo de química mineral da clorita e muscovita para o depósito de Au ± Cu do Pé Quente (limite entre municípios de Terra Nova do Norte e Peixoto de Azevedo, MT). Os estudos de química mineral seguiram a caracterização petrográfica de quatro tipologias texturais de muscovita: anédrica, radial, subeuedral e interclivagem; além de duas de clorita: anédrica e pseudomórfica. A classificação química mostrou homogeneidade entre ambas as variedades de cristais, sendo que a muscovita mostra composição fengítica, enquanto que a clorita é essencialmente brunsvigítica. O geotermômetro da clorita indica temperaturas entre 245 e 265 °C, enquanto que as pressões do geobarômetro da muscovita indicam valores entre 0,92 e 3,03 kbar. Métodos que discutem o distanciamento dos cristais de clorita para as fontes dos fluidos hidrotermais...
Keywords: Geoquímica; Depositos hidrotermais; Ouro; Crátons; Mineralogia; Petrologia; Análise com microssonda; Alta Floresta (MT)